Phonological characteristics of Malaysian speakers of English and its effect on intelligibility / Abdul Rauf Abu Hassan - Abu Hassan, Abdul Rauf (2011)
This study looks into several phonological characteristics of Malay language that differ with the phonological characteristics of English language that is most likely to interfere with the intelligibility when they interact with L1 English speakers. This study was made mainly because Malaysian and specifically students in Malaysia who practice English language seems to have problems while communicating with L1 English speaker in term of their pronunciation. This study also investigates L1 English speakers’ perceptions on pronunciation of Malay speakers of English and its effect on intelligibility. Ten Malay speakers of English and five L1 English speakers were chosen as the sample in this research. The research method included twenty sentences that contained specific phonemes, and ten sentences including consonant clusters. The Malay speakers of English were requested to take part in the process by reading aloud the two sets of sentences while being recorded. Then, the L1 English speakers were asked to listen to the recordings of the Malay speakers of English and answer the three sets of questions accordingly. The results suggested that the phonemes and consonant clusters which do not exist in the Malay sound system and syllable structure caused problems for Malay speakers of English.